Basic researchVitamin C pre-medication enhances the anaesthetic effect of ketamine-xylazine combination in the rat - Najafpour, Alireza; Sadeghi-Hashjin, Goudarz (Archives of Medical Science, 2007)
Introduction: This experimental study was designed to study the effects of ascorbic acid (vitamin C = VitC) for premedication on ketamine/xylazine anaesthesia in the rat. Material and methods: Fifty albino laboratory rats (Sprague-Dawley) of either sex were divided into five groups (A, B, C, D and E) of ten rats in each. Rats in groups C, D and E were pre-treated with 50, 100 and 150 mg/kg, respectively, of VitC. The animals in group A (control) were treated neither with VitC nor ketamine/xylazine. A combination of ketamine 5% (40 mg/kg) and xylazine 2% (5 mg/kg) was administrated intraperitoneally (I.P.) to all groups except group A. The onset and duration of hypnosis as well as vital signs were observed and recorded. Results: There was a significant (p<0.01) decrease in the onset and increased duration of anaesthesia in the animals treated with medium (group D) and high (group E) doses of VitC. Heart and respiratory rates were decreased in all anaesthetized animals, irrespective of the presence or absence of the pre-treatment and dose of vitamin C. Conclusions: VitC at 150 mg/kg administration prior to ketamine/xylazine treatment could be used to decrease the time needed to induce and to increase the duration of anaesthesia in rats. Application of VitC as a premedication agent in clinical practice, therefore, might be of interest in human and animal patients to use a lower dose of anaesthetics and, therefore, to minimize their side effects.